Tính (x^3+8):(x+2)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
8 x 1 = 8 8 x 2 = 16 8 x 3 = 24 8 x 4 = 32
1 x 8 = 8 2 x 8 = 16 3 x 8 = 24 4 x 8 = 32
8 x 5 = 40 8 x 6 = 48 8 x 7 = 56 8 x 8 = 64
5 x 8 = 40 6 x 8 = 48 7 x 8 = 56 8 x 9 = 72
1.2.3.4.5....9- 1.2.3..8 -1.2.3....8.8
=9 . [1.2.3....8] - [1.2.3..8] .1 -1.2.3..8.8
=[ 1.2.3.4...8 ] . [9-1] . 1.2.3..8.8
=[1.2.3...8 ] . 8 . [1.2.3...8].8=0 ok .
=1 x 2 x 3 x ... x 9 - 1 x 2 x 3 x ... x 8 - 1 x 2 x 3 x ... x8 x (9 - 1)
=1 x 2 x 3 x ... x9 - 1x2x3x...x8 - 1x2x3x..x8x9 + 1x2x3x..x8
=0
k cho mình nha ò ò ò ò =))))))))))
`2/3 xx 2/8 +2/3 : 8 +2/3 xx 5/8`
`=2/3 xx 2/8 +2/3 xx 1/8 +2/3 xx 5/8`
`=2/3 xx (2/8+1/8+5/8)`
`=2/3 xx 8/8`
`=2/3 xx 1`
`=2/3`
8 x 2 + 8 = 16 + 8
= 24
8 x 4 + 8 = 32 + 8
= 40
8 x 6 + 8 = 48 + 8
= 54
8 x 3 + 8 = 24 + 8
= 32
8 x 5 +8 = 40 + 8
= 48
8 x 7 + 8 = 56 + 8
= 64
`(3xx4xx7)/(5xx3xx4)=7/5`
`(2xx5xx6xx8)/(6xx2xx8xx9)=5/9`
`(4xx5xx6)/(3xx10xx8)= (4xx5xx6)/(3xx5xx2xx4xx2)= 6/(3xx2xx2)= 6/(6xx2)=1/2`
\(a,\dfrac{3\times4\times7}{5\times3\times4}=\dfrac{7}{5}\)
\(b,\dfrac{2\times5\times6\times8}{6\times2\times8\times9}=\dfrac{5}{9}\)
\(c,\dfrac{4\times5\times6}{3\times10\times8}=\dfrac{2}{4}=\dfrac{1}{2}\)
\(\dfrac{8^2.125.9^2-32.5^3.81}{20^3.3^4-6^8.5^4}\)
\(=\dfrac{2^6.5^3.3^4-2^5.5^3.3^4}{4^3.5^3.3^4-2^8.3^8.5^4}\)
\(=\dfrac{2^6.5^3.3^4-2^5.5^3.3^4}{2^6.5^3.3^4-2^8.3^8.5^4}\)
\(=\dfrac{2^5.5^3.3^4\left(2-1\right)}{2^6.5^3.3^4\left(1-2^2.3^4.5\right)}\)
\(=\dfrac{2^5.5^3.3^4.1}{2^6.5^3.3^4\left(1-810\right)}\)
\(=\dfrac{1}{2.\left(-809\right)}\)
\(=-\dfrac{1}{1618}\)
1. A) 225886 + 779 × 8
= 225886 + 6232
= 232118
B) 125 × 5 × 20 × 8
= (125 × 8) × (5 × 20)
= 1000 × 100
= 100000
C) 47286 : 2 + 14765
= 23643 + 14765
= 38408
D) 91428 - 23560 : 5
= 91428 - 4712
= 86716
3. A) 36 × 532 + 63 × 532 + 532
= 532 × (36 + 63 + 1)
= 532 × 100
= 53200
B) 679 × 123 + 679 - 679 × 24
= 679 × (123 + 1 - 24)
= 679 × 100
= 67900
C) 245 × 327 - 245 × 18 - 9 × 245
= 246 × (327 - 18 - 9)
= 245 × 300
= 73500
8 x 1 = 8 8 x 3 = 24 8 x 5 = 40 8 x 7 = 56 8 x 9 = 72
8 x 2 = 16 8 x 4 = 32 8 x 6 = 48 8 x 8 = 64 8 x 10 = 80
\(\left(x^3+8\right):\left(x+2\right)\)
\(=\left(x+2\right)\left(x^2-2x+4\right):\left(x+2\right)\)
\(=x^2-2x+4\)
\(^{\left(x^3+8\right):\left(x+2\right)}\)
=\(\left(x^3+2^3\right):\left(x+2\right)\)
=\(\left(x+2\right)\left(x^2-2x+4\right):\left(x+2\right)\)
=\(^{x^2-2x+4}\)